Hubungan Jenis Kelamin dengan Kejadian Hipertensi pada Lansia di Puskesmas Nglegok Kabupaten Blitar - Yeni Kartika Sari; Evi Tri Susanti (Journal of Ners and Midwifery, 2016)
Until now, hypertension still become a major challenge in Indonesia, because hypertension is a condition that is often found in primary health care. Gender is one of the factors that influence blood pressure that cannot be changed. Male have higher rates of hypertension than women. Aging also resulted in the increase of blood pressure. The purpose of this study was to determine the correlation of sexes and hypertension of elderly in Nglegok Public Health Center Kabupaten Blitar. This research was descriptive analytic by using cross sectional design. The population in this study was 54 people while the sample was 29 people. The data collection obtained from a medical record and analyzed by the Spearman Rank test. The results showed that there was no correlation between the sexes and hypertension of elderly in Nglegok Public Health Center Kabupaten Blitar with the Sig. 0.130. This was likely due to factors that affect hypertension was not only gender, but also age and physical activity, so that the elderly need to be stimulated to actively participate in elderly posyandu in each region, so that the activities of the elderly will increase